Treatment of diabetic ulcers with Chuang Ling Ye: systems pharmacology and functional validation reveal the mechanism of angiogenesis and inflammation abatement driven by the PI3K-AKT signaling pathway - Feng, Xiao; Yi, Nan; Zhao, Ya; Zhang, Cunyu; Chen, Yue; Wang, Qian; Yin, Xindong; Zhou, Yuanzi; Liu, Ying; Pan, Chao; Wang, Gaoyuan; Ma, Chaoqun (Frontiers in Pharmacology, 2025)
Aim of the studyDiabetic ulcer (DU), a major complication of diabetes, is characterized by complex pathophysiology and limited therapeutic options. Chuang Ling Ye (CLY) has demonstrated significant therapeutic efficacy in the treatment of DU. This study investigates the therapeutic potential of CLY for DU in vivo and in vitro, examining its mechanisms at tissue, cellular, and molecular levels.MethodsA UHPLC-MS/MS methodology was employed to identify metabolites in CLY. Network pharmacology was utilized to construct a metabolite-target network, and GO and KEGG enrichment analyses were performed to predict potential biological mechanisms of CLY in DU treatment. Furthermore, the therapeutic efficacy of CLY against DU was validated through in vitro and in vivo experiments. The mechanism of action of CLY in DU treatment was further verified using Western blot and flow cytometry.ResultsA total of 357 metabolites were identified in CLY using UHPLC-MS/MS. Our data indicate that CLY significantly promoted DU healing in vivo. In vitro experiments revealed that CLY ameliorated high glucose-induced dysfunction in HUVEC cells and upregulated the expression of angiogenesis-related proteins VEGF and CD31. Additionally, CLY significantly reduced the release of inflammatory factors in lipopolysaccharide-induced THP-1 cells, confirming its anti-inflammatory properties. These effects were attenuated following inhibition of the PI3K-Akt signaling pathway with LY294002. Consistent results were observed in vivo, elucidating the therapeutic efficacy and mechanistic basis of CLY in DU treatment.ConclusionCLY promotes DU healing by attenuating inflammatory responses and enhancing angiogenesis through activation of the PI3K-Akt signaling pathway.